Comparison of nutrients and microbial density in goji berry juice during lactic acid fermentation using four lactic acid bacteria strains. Issue 1 (4th December 2020) - Wang, Mengze; Ouyang, Xiaoyu; Liu, Yaran; Liu, Yue; Cheng, Lei; Wang, Chengtao; Zhu, Baoqing; Zhang, Bolin
Abstract: To study the effect of lactic acid fermentation of goji berry juice on the antioxidant activity and metabolism of sugars, organic acids, and amino acids, four different lactic acid bacteria were adopted in the fermentation and metabolites were analyzed. Results showed that all strains could grow well in goji berry juice and Lactobacillus brevis showed much better growth rate. Malic acid, was significantly metabolized by all bacteria. Lactic acid was detected as the most produced acidic metabolite during the fermentation, especially by Lactobacillus plantarum . In addition, inoculated with lactic acid bacteria could increase the content of biogenic amines and decrease the content of amino acids. Moreover, a significant increase of total polyphenol and antioxidant activity was found by inoculation with Lactobacillus acidophilus . Fermentation could lead to the goji berry juice more darkness, redness, yellowness, and saturation, which was more evident in L. acidophilus and L. plantarum fermented samples. Practical applications: Goji ( Lycium barbarum ) has been cultivated in large scale with more than 200, 000 t annual yield of its berry in China. However, a small percentage of them has been used for industrial processing. In the present study, four strains of lactic acid bacteria were used to ferment goji berry juice, and their growth and effect on the quality of the juice were compared. Our results will provide useful information for the development of new goji berry processing products.